2020
DOI: 10.1038/s41598-020-78735-y
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus exposure affects neuron-glia communication in the hippocampal slices of adult rats

Abstract: Zika virus (ZIKV) infection during pregnancy was associated with microcephaly in neonates, but clinical and experimental evidence indicate that ZIKV also causes neurological complications in adults. However, the changes in neuron-glial communication, which is essential for brain homeostasis, are still unknown. Here, we report that hippocampal slices from adult rats exposed acutely to ZIKV showed significant cellular alterations regarding to redox homeostasis, inflammatory process, neurotrophic functions and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…In both astrocytes and microglia, ZIKV elicited classical inflammatory responses [ 96 ], while, for astrocytes, it induced oxidative stress, mitochondrial failure, and DNA damage in astrocytes [ 97 ]. Our group have demonstrated that an acute hippocampus exposure to ZIKV is also able to induce neuroinflammation and oxidative stress, affecting neuron-glia communication [ 98 ].…”
Section: Neurochemical Changes and Molecular Mechanisms Associated With Gliotoxicitymentioning
confidence: 99%
“…In both astrocytes and microglia, ZIKV elicited classical inflammatory responses [ 96 ], while, for astrocytes, it induced oxidative stress, mitochondrial failure, and DNA damage in astrocytes [ 97 ]. Our group have demonstrated that an acute hippocampus exposure to ZIKV is also able to induce neuroinflammation and oxidative stress, affecting neuron-glia communication [ 98 ].…”
Section: Neurochemical Changes and Molecular Mechanisms Associated With Gliotoxicitymentioning
confidence: 99%
“…The association of ZIKV to other neurological manifestations have also been described and suggested, beyond that observed in congenital Zika syndrome ( Lebov et al, 2018 ; Beys-da-Silva et al, 2019 ; 2020 ; Bobermin et al, 2020 ). Molecularly, according to the review of DEGs in ZIKV infection, other brain diseases can be potentially linked to virus exposure ( Figure 6B ).…”
Section: Mechanisms: Lessons From Experimental Studiesmentioning
confidence: 95%
“…ZIKV can also affect the immunological and oxidative responses associated with astrocytes ( Ledur et al, 2020 ). Moreover, ZIKV was able to replicate in an experimental model of adult brain tissue ( Figueiredo et al, 2019 ), as well as affected neuron-glia communication in the hippocampus ( Bobermin et al, 2020 ), suggesting that neurological consequences in Zika-infected adults need more studies and clinical observations. By understanding the interaction among neurons and glial cells, preventive/therapeutic strategies may emerge.…”
Section: Mechanisms: Lessons From Experimental Studiesmentioning
confidence: 99%
“… 122 In vitro studies of human and mouse brain tissue suggest that ZIKV can replicate within human and mouse brain cells and may lead to memory and synaptic changes via virus-induced inflammation and disrupted neuronal–glial communication. 123 , 124 This suggests that patients with a history of Zika infection may be at a higher risk of neurodegeneration and need to be monitored for clinical signs.…”
Section: Neuroinvasive Zikv Infectionmentioning
confidence: 99%